Corruption, media systems and governments: contexts of prosecution and defense from the public authority in Argentina and Brasil - Coimbra Mesquita, Nuno (2015)
This article analyzes the role of political scandals at different times of the government’sactivity, with the intention to verify if news of corruption differs in electoral and non-electoral periods. We try to verify in what contexts Argentinean and Brazilian governments are more permeable to political scandals and respond more actively. We consider the electoral schedule and the type of Presidentialism in Argentina and Brazil. We argue that after an accusation of corruption in media, public officials assess risks in order to consider if their reputation were erode by not facing scandals of corruption. During electoral periods politicians fear of punishment from voters through mechanisms of electoral accountability. Finally we say that the majority Presidentialism is less permeable to allegations that coalition one. To corroborate these hypotheses we investigate responses of governments in Argentina (as a case of majoritarian Presidentialism),and in Brazil (as a case of coalitional Presidentialism).